DETECTING THE AFFECTED AREAS OF MOUNT SINABUNG ERUPTION USING LANDSAT 8 IMAGERIES BASED ON REFLECTANCE CHANGE - Suwarsono; Hidayat; Jalu Tejo Nugroho; Wiweka; Parwati; M. Rokhis Khomarudin (BRIN, 2015)
The position of Indonesia as part of a